Impact of community-based health insurance on utilisation of preventive health services in rural Uganda: a propensity score matching approach - Emmanuel Nshakira-Rukundo; Essa Chanie Mussa; Nathan Nshakira; Nicolas Gerber; Joachim von Braun (International Journal of Health Economics and Management, 2021)
The effect of voluntary health insurance on preventive health has received limited research attention in developing countries, even when they suffer immensely from easily preventable illnesses. This paper surveys households in rural south-western Uganda, which are geographically serviced by a voluntary Community-based health insurance scheme, and applied propensity score matching to assess the effect of enrolment on using mosquito nets and deworming under-five children. We find that enrolment in the scheme increased the probability of using a mosquito net by 26% and deworming by 18%. We postulate that these findings are partly mediated by information diffusion and social networks, financial protection, which gives households the capacity to save and use service more, especially curative services that are delivered alongside preventive services. This paper provides more insight into the broader effects of health insurance in developing countries, beyond financial protection and utilisation of hospital-based services.
Keywords: 330; Community-based health insurance; Enrolment; Preventive health; Inverse probability weighting; Rural Uganda; I130; I150; I100